Farming Systems and Rural Out‐Migration in Nang Rong, Thailand, and Chitwan Valley, Nepal1. (17th January 2013) - Piotrowski, Martin; Ghimire, Dirgha; Rindfuss, Ronald
Abstract: Using data from two postfrontier rural settings, Nang Rong, Thailand ( N = 2, 538), and Chitwan Valley, Nepal ( N = 876), this article examines agricultural push factors determining the out‐migration of young people age 15 to 19. We focus on different dimensions of migration, including distance and duration. Our study examines a wide array of agricultural determinants, each with its own potential effect on migration. These determinants include land tenure, crop portfolios, animal husbandry activities, and use of farm inputs. We link these proximal causes to two underlying mechanisms: risk and amenities. We examine these determinants using separate models across settings. Our results indicate that agricultural factors are significant determinants of migration in both contexts. However, different factors operate in different settings, indicating the importance of contextual variation in explaining the manner in which risks and amenities influence agricultural determinants of migration.